New Perspectives on Roles of Alpha-Synuclein in Parkinson’s Disease - Zhang, Guoxin; Xia, Yun; Wan, Fang; Ma, Kai; Guo, Xingfang; Kou, Liang; Yin, Sijia; Han, Chao; Liu, Ling; Huang, Jinsha; Xiong, Nian; Wang, Tao (Frontiers in Aging Neuroscience, 2018)
Parkinson’s disease (PD) is one of the spectrum of disorders collectively termed synucleinopathies that typified by presence of intraneuronal protein inclusions composed primarily of misfolded and aggregated forms of alpha-synuclein (α-syn), toxicity of which has been attributed to the transition from an α-helical conformation to a β-sheet–rich structure that polymerizes to form toxic oligomers, which could spread and initiate the formation of “LB–like aggregates,” by transcellular mechanisms with seeding and subsequent permissive templating. This “prion-like hypothesis” postulates that α-syn is a prion-like pathological agent and is responsible for the progression of Parkinson pathology. Moreover, involvement of inflammatory response in PD pathogenesis has been reported with excessive microglial activation and production of proinflammatory cytokines. At last, treatments that designed to block the release and uptake of pathogenic α-syn protein, especially the oligomers, to increase its extracellular clearance, and to inhibit protein assembly and transmission, seem to be available therapies to slow or halt the pathological disease progression.